Two-Warehouse Inventory Model for Non-Instantaneously Deteriorating Item Incorporating Preservation Technology, Carbon Emissions and Hybrid Payment Schemes - Limi, Anthony; Rangarajan, Kumar (Yugoslav Journal of Operations Research; Online first, 2025)
This study proposes an advanced inventory model for non-instantaneously deteriorating items, integrating preservation technology, carbon emissions considerations, price-dependent demand, and a hybrid payment scheme within a two-warehouse framework. The hybrid payment method, combining partial upfront and deferred payments, enhances cash flow flexibility, which is critical for managing financial constraints in supply chain operations. The model aims to optimize inventory management by minimizing total costs while fostering environmental sustainability. Key features include investments in green technology to reduce carbon emissions and mitigate item deterioration, along with dynamic pricing strategies to respond to market demand fluctuations. Numerical analyses validate the model, revealing that preservation technology investments significantly lower total costs by extending product shelf life, while effective carbon management reduces transportation expenses. The hybrid payment scheme also proves to be a strategic tool for balancing financial obligations and operational efficiency. Sensitivity analysis conducted using MATLAB R2024a highlights the impact of changes in key parameters, such as demandelasticity, deterioration rate, and carbon tax, on the total cost. The findings provide actionable insights for managers to enhance inventory efficiency and sustainability, particularly in cost-sensitive and environmentally regulated industries.